How Financial Aid Policy Shortchanges American Healthcare. Issue 3 (14th June 2022) - Baugh, Aaron D.; Baugh, Reginald F.
Abstract: Issue: Medical school debt is increasing. This trend may reduce access to medical school at a time of historic recognition of the need for greater openness and diversity in medical education by disadvantaging candidates who are underrepresented in medicine. The effects of high education-related debt for medical school needs greater consideration. Evidence: The implementation staircase model is employed as lens for understanding the impact of debt on trainees who are underrepresented in medicine and the healthcare system overall. Higher debt burdens are associated with worse mental health outcomes and increased odds of attrition in medical school. Trainees cite debt as a concern in considering primary care careers. Those with greater debt are less likely to pursue or remain in academic careers. Implications: The current financial aid system's reliance on high debt burden undermines goals to improve the representation of underrepresented candidates in primary care and academic medicine. Alternative models requiring less debt could facilitate the creation of a more diverse workforce in healthcare.